2005
DOI: 10.1038/sj.onc.1209121
|View full text |Cite
|
Sign up to set email alerts
|

The p53-inducible apoptotic protein AMID is not required for normal development and tumor suppression

Abstract: AMID is an apoptosis-inducing factor (AIF)-homologous and mitochondria-associated protein that has been implicated in caspase-independent apoptosis. Transcription of human AMID gene is upregulated by p53 and downregulated in tumors in comparison to their matched normal tissues, suggesting the possibility that AMID is involved in the downstream effects of p53. To investigate the physiological functions of AMID, we generated AMID-deficient mice by gene targeting. AMID-deficient mice are viable and fertile, devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
21
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 29 publications
3
21
0
Order By: Relevance
“…These results show in detail the actual process of nuclear translocation of endoG and AIF and they question the proposed role of AMID in apoptosis [8,31,32]. They are also supported by a recent study demonstrating that knockout mice lacking AMID are viable and apparently normal and do not display any differences in development from wild-type mice [58]. Moreover, the authors also found no differences in the frequencies of natural tumor occurrence or 3-methylcholanthrene-induced sarcoma in these mice compared to wild type.…”
Section: Translocation Of Endog Aif and Amid To Nucleussupporting
confidence: 43%
“…These results show in detail the actual process of nuclear translocation of endoG and AIF and they question the proposed role of AMID in apoptosis [8,31,32]. They are also supported by a recent study demonstrating that knockout mice lacking AMID are viable and apparently normal and do not display any differences in development from wild-type mice [58]. Moreover, the authors also found no differences in the frequencies of natural tumor occurrence or 3-methylcholanthrene-induced sarcoma in these mice compared to wild type.…”
Section: Translocation Of Endog Aif and Amid To Nucleussupporting
confidence: 43%
“…This is consistent with the apparent lack of an extended N-terminal mitochondrial targeting sequence analogous to that found in AIF (18,21). AIF-M2 is transcriptionally up-regulated by p53 and by genotoxic chemicals, suggesting that it might contribute to the arrest of cell growth on exposure to such agents (23). AIF-M2 is a DNA-binding protein with nicotinamide coenzyme-dependent oxidoreductase activity, and it is usual for the purified protein to contain 6-hydroxy-FAD (19).…”
supporting
confidence: 61%
“…Such a model would require that AIF-M2 has a physiological role in preventing apoptosis. As with AIF, knock out of AIF-M2 protein expression has no effect on both normal and tumor cell viability (23), thus pointing to other sources of ROS to maintain ROS production for survival signaling (17). With AIF knock-outs there is increased sensitivity to peroxide-induced apoptosis, but comparable studies with AIF-M2 knockouts have not been reported.…”
Section: Discussionmentioning
confidence: 78%
“…(36) Although expression of AMID is upregulated by p53 and genotoxins, and downregulated in many tumors, analysis of AMID À/À mice indicates that AMID is not essential for normal development and provides no evidence for any role in p53-dependent tumor suppression. (38,39) These studies imply that AMID is unlikely to be part of an AIF-dependent pathway, and its cellular localization makes it improbable that it compensates for loss of AIF in neurons. Although ROS were not directly measured, indirect evidence implied that AIF-deficient ES or HeLa cells exhibited similar or marginally lower levels of ROS to AIF-expressing cells in unstressed conditions.…”
mentioning
confidence: 96%